DEVELOPMENT OF AUGMENTED REALITY ASSISTED LEARNING MEDIA TO IMPROVE CONCEPT UNDERSTANDING OF CHEMICAL BONDING TOPICS - Isnanik Juni Fitriyah; Agung Mulyo Setiawan; Muhammad Fajar Marsuki; Erti Hamimi (Jurnal Pembelajaran Sains, 2020)
The chemical bonding is one of the topics of discussion in chemistry that studies atomic and molecular structures that are difficult for students to understand because of their microscopic nature. Augmented Reality (AR) technology can combine three-dimensional virtual world objects into a real three-dimensional environment. Therefore, learning media were developed with the help of Augmented Reality (AR) for chemical bonding materials. This research is a research and development (R&D), with a modified 4D development model by Thiagarajan. The stages starting from define, design and develop. The data collection instrument used the material expert validation test instrument, the media expert and readability test to students. The data analysis technique used percentage descriptive analysis.The validity test of the material, media and readability test showed that the results of the media percentage were 87.9%, 79.87% and 87.6%, respectively. This percentage is included in the very valid category without revision.Thus, it can be concluded that the Augmented Reality media in the Chemical Bond material developed is declared very suitable for use in learning.